The concentration of adrenaline and noradrenaline in the serum of dogs under the influence of calcium channels blockers - Milanović Tamara (Praxis Medica, 2015)
The most important characteristic of calcium channels is selective regulation of slow incoming stream of calcium into the cell tissue providing the slow increasement of action potential. Such tissues include smooth muscles of blood vessels, cardiocytes and heart noduses (AV and SA node). Different calcium antagonists have different effects on previous tissues due to their different chemical formula. Verapamile, Nifedipin and Diltiazem are the most frequently used of all. Their commonest characteristic is blocking the calcium channels causing vasodilatation of blood vessels as well as negative inotropic and chronotropic influence. By blocking the incoming calcium through slow channels of myofibrils of smooth muscles, the antagonists of calcium decrease the quantity of available calcium for contraction which causes vasodilatation. The most famous and most frequently used calcium antagonist is Verapamile. In terms of electrophysiology, Verapamile inhibits action potentials of heart noduses, especially the AV node, where the slow incoming of calcium is the most important for depolarization. Prolongation of the efective refractory period of SA node causes the heart frequency decreasement while prolongation of the effective refractory period of AV node slows down the work of chambers in case of flater and fibrillation of atriums. The molecules of calcium-bonding protein called kalmodulin are located in synaptic endings. Each kalmodulin can bond four calcium ions providing transfer into active calcium-kalmodulin complex which activates the kinase protein. Activated kinase protein starts the exocytosis of neurotransmitters into synaptic gap. Apart from activating kinase protein, calcium-kalmodulin complex also starts the activity of calcium pump presynaptic membrane which pumps calcium out of presynaptic ending stopping the further exocytosis of neurotransmitters into synaptic gap. Taking into consideration the fact that opening the calcium channels on membrane of presynaptic ending is necessary to free the neurotransmitter out of the vesicle, the aim of our work is to study whether Verapamile has effects on the membrane of presynaptic endings of sympathetic nervous system checking the level of catecholamine in serum. The experiment was conducted in 6 healthy dogs which were, after 10-minute-infusion (0.9% NaCl), treated with intravenous bolus veramapile injections in three occasions, in every 5 minutes, until the first signs of intoxication had appeared. This caused bradycardia, heart rhythm disorder and blood pressure drop. In order to determine the level of catecholamine, blood was taken sequentially, in every 5 minutes, before the new dose of verapamile was given. Verapamile (given intravenous) significantly decreases the concentration of adrenaline and noradrenaline in the serum of dogs.